Lessons learned from REXUS12'S Suaineadh Experiment : Spinning deployment of a space web in milli gravity - Sinn, Thomas; McRobb, Malcolm; Wujek, Adam; Skogby, Jerker; Rogberg, Fredrik; Wang, Junyi; Vasile, Massimiliano; Tibert, Gunnar (2013)
On the 19th of March 2012, the Suaineadh experiment was launched onboard the sounding rocket REXUS 12 (Rocket Experiments for University Students) from the Swedish launch base ESRANGE in Kiruna. The Suaineadh experiment served as a technology demonstrator for a space web deployed by a spinning assembly. Following launch, the experiment was ejected from the ejection barrel located within the nosecone of the rocket. Centrifugal forces acting upon the space web spinning assembly were used to stabilise the experiment’s platform. A specifically designed spinning reaction wheel, with an active control method, was used. Once the experiment’s motion was controlled, a 2 m by 2 m space web is released. Four daughter sections situated in the corners of the square web served as masses to stabilise the web due to the centrifugal forces acting on them. The four daughter sections contained inertial measurement units (IMUs). After the launch of REXUS12, the recovery helicopter was unable to locate the ejected experiment, but 22 pictures were received over the wireless connection between the experiment and the rocket. The last received picture was taken at the commencement of web deployment. Inspection of these pictures allowed the assumption that the experiment was fully functional after ejection, but probably through tumbling of either the experiment or the rocket, the wireless connection was interrupted. A recovery mission in the middle of August was only able to find the REXUS12 motor and the payload impact location.